ANALISIS PENGARUH KUALITAS PRODUK DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATIK NATURAL INDIGO DYED (Studi Kasus Pada Konsumen Produk Batik Merek The Bluesville) - Taufiq Shaleh; Apriatni Endang Prihatini (Universitas Diponegoro, 2017)
Batik is one of the product of fashion industry originated from Indonesia which has already been recognized by the world. It is one of the form of Indonesia’s indigenous culture with big potential to contribute in increasing national economy on creative industry sector. One of the innovation of batik is natural indigo dyed batik, which uses the fermentation of Indigofera tinctoria plant in the coloring process, and The Bluesville is one of the local brand that’s producing this kind of batik. In the last three years, the sales of The Bluesville continue to increase, eventhough it has not reached the company’s sales target. This matter is caused by the lack of awareness from the consumer about the excellence of the natural indigo dyed batik fabrication. Higher competition require the company to set a strategy to keep innovating and improving the product quality that they produce.The type of this study is an explanatory research, with population of 100 respondents that use natural indigo dyed batik from The Bluesville. The sampling used in this study is a non-probability sampling, and the sampling technique is purposive sampling. The data is collected with a questionnaire. Data analysis method used in this study are correlation, simple regression, multiple regression, and classic assumption test all using SPSS.This study concludes that the quality of a product as well as brand awareness effect on the consumer’s purchasing decision, both partial and simultants. Brand awareness variable has a higher effect than product quality variable.Based on those results, we suggest The Bluesville to improve the brand awareness level, so that the consumer will be more aware of the product and eventually increasing the purchasing decision of the natural indigo dyed batik from their company.